ChemInform Abstract: Approach to Trisubstituted 1H‐Pyrroles from Alkynoates and Amines Mediated by tert‐Butyl Perbenzoate. Issue 36 (15th August 2013) - Liu, Weibing; Tan, Liquan; Zhou, Peng; Chen, Cui; Zhang, Qing
Abstract The tandem cyclization of 2 equiv.